JUMLAH BIBIT PER LUBANG DAN JARAK TANAM BERPENGARUH TERHADAP HASIL PADI GOGO (Oryza sativa L.) DENGAN SYSTEM OF RICE INTENSIFICATION (SRI) DI LAHAN KERING - Hery Christanto; I Gusti Ayu Mas Sri Agung (Environmental Research Center (PPLH) of Udayana University, 2014)
Water availability is a major limiting factor to the growth and yield of rainfed rice. Systemof Rice Intensification (SRI), which is an efficient method of planting rice, particularly inthe use of water, number of seeds per hill and time of transplanting seedlings, has beenapplied generally in irrigated rice but it is rarely practiced in rainfed rice.A field experiment, which was aimed to study the effect of number of seed/hill and variationof plant spacing on the growth and yields of rainfed rice with SRI (System of RiceIntensification), was conducted during dry season from April until September 2012. Thelocation was at Patemon Village, District of Seririt, Buleleng Regency, Bali, at the altitudeof 100 meter asl. In this experiment a completely randomized block design was used and thetreatment were arranged factorially. The first factor was the number of seeds (1,2,3 and 4)/hill and the second one was the plant spacing (20 cm x 20 cm, 25 cm x 25 cm and 30 cm x 30cm). All treatments were replicated three times.The results of the experiment showed that the interaction between one seed/hill and plantspacing of 30 cm x 30 cm resulted in significantly (P<0.05 and P<0.01) the highest fresh(4.387 ton/ha) and oven dry weight of grains (3.633 ton/ha), oven dry weight of 1000grains (20.920 g) and the harvest index (31.163%). The gross margin analysis indicatedthat the variable costs were higher than the gross income for all treatment, due to high costof watering